The Responsibility of the Notary in Providing Legal Information to the Parties on the Deed He Made - Chilsy Indiyarti; Sri Kusriyah; Peni Rinda Listyawati (Sultan Agung Notary Law Review, 2022)
Legal Counseling is carried out by providing clear, directed explanations, so that the meaning and purpose of the authentic deed are easily understood and understood by the parties. Sometimes people only provide explanations and documents without knowing the legal issues. Article 15 paragraph paragraph 2 letter e of Act No. 2 of 2014 explains that, "in addition to the authority as referred to in paragraph (1), the Notary is also authorized to: provide legal counseling in connection with the making of the Deed." Here it is explained that every notary is obliged to explain the responsibility to provide legal counseling to the parties/clients. This research purposed to review and analyze the Responsibilities of the Notary in providing legal counseling to the parties for what he did in the City of Kendari, and to examine and analyze the obstacles and solutions of the notary in providing legal counseling to the parties for what he did. The research approach method used in this research was an empirical juridical research method. The type of data used in this research Primary Data includes Act No. 2 of 2014 concerning Notary Positions and Secondary Data containing books and documentsother supporters. Collecting research data with interview techniques and study of documents or library materials. The data analysis method used in analyzing the data is a qualitative approach in order to obtain descriptive data. The results of the study show that: First, the Notary's responsibility in providing legal counseling is only to provide advice to the parties/clients, it is the client who has the decision in the deed as long as it does not conflict with Article 1320 of the Criminal Code, so that there are no consequences.law in the future. Second, the barriers are competence, clients who do not explain in detail, communication, differences in interpretation, and client characteristics as well as upgrading solutions for notaries, supporting documents, communication skills, discussion for solutions, and psychological approaches.